High Electrochemical Versatility and Applicability with Metal Phthalocyanines Carrying Peripheral 2,3-dihydro-1H-inden-5-yloxy Substituents: Rich Redox Behavior, Oxygen Electrocatalysis and Electrochromism - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN; ODABAŞ, ZAFER (ELECTROCHEMICAL SOC INC, 2018)
The presence of cobalt(II), iron(III) and manganese(III) in the peripherally 2,3-dihydro-1H-inden-5-yloxy substituted phthalocyanine (Pc) core enriched their redox character in non-aqueous media with additional reversible metal-based reduction and oxidation couples, compared to their metal-free and tin(IV) Pc analogues displaying only Pc ring-based redox processes. The existence of trace amount of dioxygen in the electrolyte system was observed to considerably influence the redox behaviors of FePc and MnPc. As a result of the enhanced interaction between dioxygen and the central metal, the FePc showed much higher catalytic performance for oxygen reduction reaction than those of the others. It was also nearly insensitive to the presence of methanol. The comparison with the Pt-based catalyst showed that it could be a good alternative to the platinum as cathode catalyst, especially in direct methanol fuel cells. Furthermore, the association of the redox processes of metal Pcs with distinct spectral and color changes pointed out the possibility of their application as electrochromic materials. Langmuir Blodgett film of Mn(Cl)Pc compound on the indium tin oxide glass behaved as ideal neutral and cathodic coloring material, displaying red to green and red to purple color changes between its cationic forms with fast response time and high optical stability. (C) 2018 The Electrochemical Society.
Keywords: SPECTROELECTROCHEMICAL CHARACTERIZATION; MANGANESE PHTHALOCYANINE; BIS-PHTHALOCYANINES; REDUCTION REACTION; METALLOPHTHALOCYANINES; CATALYSTS; ELECTROPOLYMERIZATION; ELECTROREDUCTION; COMPLEXES; COBALT